Modification of Online Communication in the Context of Culturally Determined Features of Communicative Behavior - S. V. Ivanova; O. E. Nosova (Дискурс профессиональной коммуникации, 2025)
This study investigates the communicative behavior of English-speaking professionals in institutional online exchanges. The background for this research lies in the growing importance of digital communication in business and the recognized need in linguistics for a deeper understanding of its pragmatic and linguacultural aspects, especially as remote work and international collaborations expand. The purpose of the study is to establish the specifics of the manifestation of distancing in institutional online communication through reference to its verbal markers. The empirical material comprises transcripts of earnings calls from a prominent American corporation, offering authentic examples of contemporary business discourse in a teleconference format. Communicative-pragmatic and linguacultural approaches employed to reach the goal preconditioned the use of definitive, contextual, and communicative functional methods. The communicative-pragmatic perspective of the study was focused on identifying the features of the verbal behavior of communicants, manifested in the preference for certain communication strategies within the digital communication format. The linguacultural focus of the study made it possible to reveal the linguistic embodiment of communication strategies as well as to analyze the correlation of linguistic analysis data with culturally specific features of speech behavior. The main result of the analysis reveals a discernible trend towards reduced distancing in English-language business online communication compared to traditional offline discourse. This suggests a significant adaptation of culturally ingrained communication norms in response to the affordances of digital formats, prioritizing immediacy and perceived closeness. The relevance of this research extends to tracking best practices in online professional communication, particularly in cross-cultural interactions where perception of subtle changes in communicative norms is vital for effective collaboration and relationship building in the digital age. The prospects of the investigation suggest further study of the problems associated with the shifts in the boundaries of social communication in the framework of Internet communication.